The Effect of Milling and Sintering Methods on the Translucency of Polychromatic Zirconia Ceramics - Akbar, Nasreen. (Tufts University. Tisch Library., 2022)
Thesis (M.S.)--Tufts University, 2022.; Submitted to the Dept. of Posthodontics.; Advisor: Ali Muftu.; Committee: Aikaterini Papathanasiou, Aikaterini Kostagianni, Yukio Kudara, and Matthew Finkelman.; Keyword: Dentistry.